Cytoprotective effect of lygodium venustum Sw. (Lygodiaceae) against mercurium chloride toxicity - Figueredo, Fernando G. (2016)
Mercury is a very dangerous metal when humans come into contact with it, whether through the air or skin or by ingestion. The aim of this work was to investigate the possible effects of the ethanol extract and fractions of Lygodium venustum Sw. against mercurium chloride toxicity towards Escherichia coli strain ATCC25922. The polyphenols and flavonoids present in the extract and fractions were quantified in mg equivalent of gallic acid/g sample and mg equivalent of quercetin/g sample, respectively. The in vitro FRAP method demonstrated the antioxidant activity of the samples. The antibacterial activity of the natural products was evaluated by microdilution method and by assays to elucidate the possible cytoprotective action when combining the natural products samples and mercurium chloride, utilizing the extract and fractions at a subinhibitory concentration. The results obtained in this work indicate that the ethanol extract and fractions of L. venustum are an alternative source of natural products with cytoprotective action, where this protection is correlated with antioxidant and chelating activity, due to the presence of total phenols and flavonoids.